Dedicatórias e dedicatários de «vidas» devotas e de santos em Portugal (séculos XVI-XVIII): entre a protecção e a devoção - Paula Almeida Mendes (Universidade do Porto, 2012)
The background of this study is the problem of the reading of works on spirituality, in the XVI-XVIII centuries, in Portugal, especially saints and devoute «Lives», and aims to present a list of their dedications and people to whom they were addressed, trying to call attention to some issues that relate not only to the readings and spiritual practices or devout, but also the relationships with the authors and/or the various religious orders with influential figures of the time, today mostly virtually unknown.